2008
DOI: 10.1103/physrevb.77.224514
|View full text |Cite
|
Sign up to set email alerts
|

Vortex dynamics and critical current in superconductors with unidirectional twin boundaries

Abstract: We have studied the dynamics of vortices interacting with unidirectional twin boundaries ͑TBs͒ in a superconductor using molecular-dynamics simulation based on the overdamped equation of vortex motion. Currentvoltage curves and critical currents have been calculated as a function of vortex density. We found that the critical current as a function of vortex density reveals a staircase pattern and this pattern depends on the pinning strength. This behavior corresponds to discontinuous change of vortex configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…10 The onset of different dynamical phases as a function of external driving has been observed in various overdamped systems, including colloids and vortices moving over q1D periodic substrates, but only for a driving force applied parallel to the substrate periodicity direction. In those systems there is generally a disordered flow phase above depinning 7,14,47,48 with a transition to a moving ordered phase at higher drives 14,47,48 ; however, negative differential conductivity does not occur. For systems of particles moving over 2D periodic substrates, such as egg carton or muffin tin potentials, negative differential conductivity can arise 18,20,[49][50][51] .…”
Section: Collective Effectsmentioning
confidence: 99%
“…10 The onset of different dynamical phases as a function of external driving has been observed in various overdamped systems, including colloids and vortices moving over q1D periodic substrates, but only for a driving force applied parallel to the substrate periodicity direction. In those systems there is generally a disordered flow phase above depinning 7,14,47,48 with a transition to a moving ordered phase at higher drives 14,47,48 ; however, negative differential conductivity does not occur. For systems of particles moving over 2D periodic substrates, such as egg carton or muffin tin potentials, negative differential conductivity can arise 18,20,[49][50][51] .…”
Section: Collective Effectsmentioning
confidence: 99%
“…Numerical studies of vortex behavior in the presence of planar defects range from solving the full time-dependent Ginzburg-Landau equations [29][30][31][32] to more approximate descriptions [33][34][35][36][37] of vortices in two-dimensional thinfilm and three-dimensional bulk samples as structureless pointor string-like objects that are studied with either Monte Carlo simulations or Langevin dynamics methods. The experimentally detected anisotropy of pinning and transport has been observed in numerical simulations of twinned superconductors [38,39] with thermal fluctuations being enhanced and vortex motion facilitated within defect planes. Reichhardt et al identified three phases of flux flow in London-Langevin studies of driven vortices subject to planar pinning, viz.…”
Section: Introductionmentioning
confidence: 83%
“…The red magnified area represents the GB model and the GB is modeled as an attractive well, 2d is the effective width of the GB and d is taken as 0.15λ . [22,24,28] In the GB region, a series of red dots indicates dislocations, and the red arrows acting on vortices denote the directions of electric forces. H and I refer to the applied magnetic field and transport current, respectively.…”
Section: Model For Vortex Dynamicsmentioning
confidence: 99%
“…[21][22][23] Although numerous studies of thin films and bulk samples have evaluated the influence of grain boundaries (GBs) on vor-tex motion, they mainly focused on the circumstances of parallel GBs or a single GB. [22][23][24][25] As is well known, the role of the GB which can be changed from a barrier to an easy-flow channel is intrinsically determined by the competitive effect associated with the action on vortex between in the GB and intragranular region, and also affected by the angle between the grain boundary and the applied current based on previous work. [26] The investigations on random GB networks with complex orientations which can model polycrystalline materials also play a crucial role in gaining a deeper knowledge about grain boundary mechanism on vortex motion.…”
Section: Introductionmentioning
confidence: 99%